Upcycling waste tilapia (oreochromis niloticus) scales through a decellularization process for extracellular matrix extraction - Fernan M Arellano; Ronald Bual; Zesreal Cain Bantilan; Johnel Alimasag; Jemwel Aron; Lean Baclayon; Michael John Nisperos; Kit Dominick Don Valle; Princess Grace Ducao; Gladine Lumancas; Job Jr Pague; Marionilo Jr Labares; et al. (Materials Research Express, 2024)
Tilapia scales, typically regarded as low-value biological waste, possess valuable organic components such as collagen and inorganic components such as hydroxyapatite. Converting these wastes into functional biomaterials like decellularized extracellular matrix (dECM) contributes to long-term fish waste management to achieve sustainable fish consumption and promote a circular economy by creating a product with a high market value. Triton X-100 (TX-100) and Sodium-dodecyl sulfate (SDS) at varying concentrations (0.1%, 0.5%, and 1%) are utilized to extract the extracellular matrix. The study aims to evaluate the effectiveness of these agents in decellularizing the scales and producing a suitable dECM scaffold. Histological analysis using H&E staining revealed a significant decrease in cellular components in the decellularized samples. This was supported by the dsDNA quantification results showing the highest removal rate of 96% in the samples treated with 1% SDS. Attenuated Total Reflectance-Fourier-transform infrared (ATR-FTIR) spectra showed the amide peaks (Amide A, B, I, II, and III) indicating the presence of type I collagen. The confirmation of type I collagen was further supported by the analysis of SDS-PAGE images, which displayed the presence of α 1 and α 2 chains, β -dimer, and the γ -band. Among the dECM, samples treated with 0.1% TX-100 exhibited the highest protein content, averaging 593.33 ± 17.78 μ g mg ^−1 while 1% SDS showed the lowest protein content averaging 61.33 ± 24.03 μ g mg ^−1 . All dECM samples demonstrated protein denaturation temperatures ranging from 70–75 °C. This study presents baseline data of the single chemical decellularization treatment method utilized to extract ECM from tilapia scales and its resulting dECM. Further research is recommended to assess the biocompatibility and cytotoxicity of the produced dECM and explore its potential applications.